2006
DOI: 10.1091/mbc.e05-08-0735
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Src to Na+/K+-ATPase Forms a Functional Signaling Complex

Abstract: We have shown that ouabain activates Src, resulting in subsequent tyrosine phosphorylation of multiple effectors. Here, we tested if the Na ؉ /K ؉ -ATPase and Src can form a functional signaling complex. In LLC-PK1 cells the Na ؉ /K ؉ -ATPase and Src colocalized in the plasma membrane. Fluorescence resonance energy transfer analysis indicated that both proteins were in close proximity, suggesting a direct interaction. GST pulldown assay showed a direct, ouabain-regulated, and multifocal interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
405
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(444 citation statements)
references
References 49 publications
25
405
2
3
Order By: Relevance
“…Binding of TCTP to the a1 subunit of Na,K-ATPase induces the release and activation of Src Recent studies suggest that phosphatidylinositol 3-kinase (PI3K) binds to the N-terminal proline-rich motif of Na,K-ATPase a subunit and that partial inhibition of Na,K-ATPase by ouabain induces Src binding to the Na,K-ATPase a subunit (Yudowski et al, 2000;Tian et al, 2006). We found that TCTP bound to the Na, K-ATPase a subunit partially inhibits its pumping activity (Jung et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding of TCTP to the a1 subunit of Na,K-ATPase induces the release and activation of Src Recent studies suggest that phosphatidylinositol 3-kinase (PI3K) binds to the N-terminal proline-rich motif of Na,K-ATPase a subunit and that partial inhibition of Na,K-ATPase by ouabain induces Src binding to the Na,K-ATPase a subunit (Yudowski et al, 2000;Tian et al, 2006). We found that TCTP bound to the Na, K-ATPase a subunit partially inhibits its pumping activity (Jung et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been suggested that Src interacts with at least two cytoplasmic domains of Na,K-ATPase a subunit, and that this binding keeps Src in its normally inactive form, whereas binding of ouabain to the ectodomain of a subunit changes Src into its active form through a conformational change in the enzyme (Tian et al, 2006). In the current studies, we showed that Src, apparently tethered to the Na,K-ATPase a subunit, is released and activated by TCTP binding to the a subunit (Figure 1) in human breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter interaction keeps Src in an inactive state. Binding of cardiotonic steroids such as ouabain to the Na/K-ATPase disrupts the latter interaction, resulting in an activation of the pump-associated Src (6). Besides Src, the ␣1 Na/K-ATPase has many interacting partners including phosphoinositide 3-kinase, inositol triphosphate receptor, adducin, ankyrin, and caveolin-1 and is actively involved in multiple cellular processes such as intracellular Ca 2ϩ regulation and caveolae formation (3,(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%